(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was conducted to survey the incidence of mango gall midge(Procontarinia matteiana Kieffer & Cecconi) in South Kordofan State, Sudan. Twenty -two sites were visited. All inspected mango trees were infested. Field observations on thelife cycle of P. matteiana showed that egg and larval periods lasted 7-10 days, while thepupal stage took 5-7 days. The survey concluded that P. matteiana is widely distributedin South Kordofan State. Further studies on the life cycle, distribution and economicimportance of the mango gall midge is needed.